Organizational culture and leadership behaviors: is manager’s psychological health the missing piece? - Dextras-Gauthier, Julie; Gilbert, Marie-Hélène; Dima, Justine; Adou, Laetitia Bomoya (Frontiers in Psychology, 2023)
Background In a context where organizations struggle to attract and retain highly qualified workers, organizations need to prioritize the psychological health of employees as a retention factor. To do so, they need to provide a healthy work environment. As an integral part of the employee experience, managers are an important factor in employee retention. In past studies, researchers have focused on the importance of leadership in boosting employees’ health without, however, considering factors encouraging such behavior in managers. Recently, some scholars have become interested in managers’ health as a resource allowing them to adopt good leadership behavior. Indeed, these studies reveal interesting links between managers’ emotional state and their behavior as leaders. Other studies, underscore the importance of considering the organizational context to better understand managers’ psychological health that may influence their leadership behaviors. This study proposes to examine the complex process by which organizational culture influences managers’ psychological health, which acts as a resource favoring the adoption of good leadership behaviors that are known to be constructive and have positive effects on employee. Methods Path analyses with the CALIS procedure SAS software, version 9.4 were conducted on a sample of 522 managers in three healthcare facilities in the province of Quebec, Canada. Results The results revealed that group culture is associated with the two indicators of managers’ psychological health at work. The results also demonstrated that managers’ psychological distress at work is positively related to transactional and laissez-faire leadership styles whereas psychological well-being at work is positively related to transformational and transactional leadership. Concerning indirect associations, there is a significant and positive indirect association between group culture and transformational leadership and there is also a significant and negative association between group culture and laissez-faire leadership. Finally, there is also an indirect association between hierarchical culture and transactional leadership. Conclusion Our study provides a more in-depth understanding of the relationship between organizational culture and leadership styles. More specifically, our findings highlight the benefits of implementing a group organizational culture to enhance psychological well-being, reduce psychological distress symptoms and promote good leadership behaviors.